2015
DOI: 10.1175/wcas-d-14-00039.1
|View full text |Cite
|
Sign up to set email alerts
|

Drought Adaptation and Climate Change Beliefs among Working Ranchers in Montana

Abstract: 24Agricultural producers may be particularly vulnerable to climate impacts such as 25 drought. To better understand how ranchers respond to ongoing drought, and the 26 relationship between climate change beliefs and drought adaptation, in-depth interviews 27 with working ranchers were conducted. Ranchers described drought conditions as 28 unprecedented and detailed the interacting impacts of drought and other non-climatic 29 stressors. They viewed adaptation as critical and employed a wide range of responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…In the present study, ranchers stated their principal reason for adopting any new agricultural practice would be for profitability. This result is consistent with several other studies that determined economic factors ( Smit and Skinner 2002 ; Kachergis et al, 2013 ; Yung et al, 2015 ) as the key determinant for implementing new agricultural practices. However, unlike other rancher volunteer programs, such as environmental quality incentive programs (EQIP; funded by USDA-NRCS), the BQA program uniquely focuses on animal health.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, ranchers stated their principal reason for adopting any new agricultural practice would be for profitability. This result is consistent with several other studies that determined economic factors ( Smit and Skinner 2002 ; Kachergis et al, 2013 ; Yung et al, 2015 ) as the key determinant for implementing new agricultural practices. However, unlike other rancher volunteer programs, such as environmental quality incentive programs (EQIP; funded by USDA-NRCS), the BQA program uniquely focuses on animal health.…”
Section: Discussionsupporting
confidence: 93%
“…Findings that most farmers in this region attribute drought to natural cycles and express skepticism in anthropogenic climate change are consistent with previous studies (Yung et al 2015;Liu et al 2014). Divergent from previous conclusions that belief in natural cycles both reduces ranchers' sense of agency to act and facilitates optimism that a cyclically changing climate will return to normal (Yung et al 2015), I nd that many farmers believe that climate change is cyclical, while also asserting concerns that those cycles will get worse.…”
Section: Farmers Discuss Changes In Terms Of Weather Ongoing Cycles and Harsh Geographysupporting
confidence: 91%
“…Across interviewees, farmers were adapting to climate impacts irrespective of how they described weather events and trends, or whether they believed in anthropogenic climate change. In addition to shortterm adaptive measures in response to climate change impacts (Yung et al 2015; Takahashi, Mano, and Otsuka 2019), I found that farmers in Siskiyou were also implementing a range of long-term adaptive management practices and livelihood strategies in response to climate change impacts, which many expressed an intent to continue into the future, even after the drought or smoke abated. While farmers elsewhere have identi ed economic factors, like reduced costs and increased e ciency, as the primary motivation for adopting conservation (Burke and Running 2019) and climate mitigation practices (Davidson et al 2019), I found a deeper core set of motivations.…”
Section: Farmers Discuss Changes In Terms Of Weather Ongoing Cycles and Harsh Geographymentioning
confidence: 99%
“…Ranchers' decisions about drought adaptation are influenced by both the specific biophysical changes occurring on their rangelands as well as social and economic processes, including commodity prices, trade policy, government drought relief programs, family finances, risk perception, available technology, and social norms. In some cases, experiences with past drought, skepticism about climate projection, risk aversion, and social norms interact in ways that reduce investments in long-term adaptation (Yung et al, 2015). Understanding drought adaptation on rangelands requires examining the ways that biophysical, economic, and social processes interact across multiple scales to both enable and constrain decisions about drought adaptation, which can be facilitated by asking the following questions: How do past ecosystem responses to drought influence the assumptions that producers make about future change?…”
Section: Thrive In Interdisciplinary Teamsmentioning
confidence: 99%